KAJIAN KONSERVASI BUAH MERAH MELALUI KULTUR JARINGAN TANAMAN; EKSTRASI , FRAKSINASI BUAH, UJI ANTIOKSIDAN, DAN UJI ANTIDIABETIK - Sumarnie Hasto Priyono (Jurnal Teknologi Lingkungan, 2008)
Buah merah (Pandanus conoideus Lam.) Pandanaceae has several local name in Kelila, Wamena – Papua based on its size, fruit colo, leaf color and taste. It has wide distribution and can be found low land to high land. Buah merah contains valuable nutrients and bioactive compounds in abundant/high concentration, such as: â-caroten, tocopherol, fatty acids (oleic acid, linoleic acid, linolenic acid and decanoic acid). Its cultivation had been done ocal people but not extensively. The easiest way of buah merah propagation was by separating buah merah seedling and stem cutting or byplanting its.The aim of the study were to compile the data that support plant identification of buah merah from Kelila, Wamena-Papua, to study is potency for antioxidant and antidiabetic properties and determine the best media in tissue culture for producing buah merah planlet. The result showed that shoot bud from stem explant cultured in media combination of MS + IBA (2 mg/l) + BA(5 mg/l) produce 10 plantlets, while callus came from leaf tip explant cultured in media combination of MS + BA (5mg/l)+TDZ (0.02 mg/l) The antioxidant test showed that ethyl acetate fraction had good antioxidant activity LC 50 (0.253) while petroleum ether fraction showed good antidiabetic properties with 0.5 % (0.560), 0.25 % (0.593) and control is 0.633.